THE EFFECT OF Cosmos caudatus LEAVES EXTRACT ON MORTALITY OF THE BLACK CUTWORM PESTS (Agrotis ipsilon) - Rizka Efi Mawli; Devi Anggraini Putri (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Cosmos caudatus (Asteraceae) is one of Indonesia biodiversity which is usually used as a refugia plant on several crop fields. In Indonesia, this plant is widely consumed as salad and herbal medicine as well. The aimed of this study is to see the effect of C. caudatus leaves extract on mortality of Agrotis ipsilon known as the black cutworm pests. C. caudatus leaves were collected on Surabaya East Java, Indonesia. The leaves were extracted by using maceration technique with ethanol 96% for 3x24 hours. After that, this research was conducted by observing the effect of ethanol extract from C. caudatus leaves with a concentration of 20; 15; and 10% on each group of A. ipsilon. The mortality assessment was made by determining the quantity of the death cutworms on 24, 48, and 72 hours. The result showed that the extract significantly reduced growth of A. ipsilon with LC50 value of 13.29% at 72 hours. Therefore, C. caudatus leaves extract is recommended as a biopesticide agent.